Accounting for the Impact of Heavy Truck Traffic in Volume–Delay Functions in Transportation Planning Models - Yun, Seongsoon; White, Wade W.; Lamb, Daniel R.; Wu, Yongqiang (Transportation research record, 2005)
Truck traffic accounts for a substantial fraction of the traffic stream in many regions and is often the source of localized traffic congestion. This paper presents the analysis and findings that recommend updated volume–delay relationships for transportation planning models that account for total volume, roadway capacity, and the mix of heavy truck traffic. The traditional Bureau of Public Roads function representing the speed–flow relationships for roadway facilities is modified to include the impact of truck traffic specifically. Several new speed–flow functions based on microsimulation results for freeways and urban arterials have been developed.